Concretization of Integral Reality Theory with the Video Assistant Referee System: Analysis of The Football Competitions of Metropolitan Municipality Erzurumspor, One of The Sportoto Super League Teams, within The Season 2018-2019 - Ülhak Çimen (Türk Spor ve Egzersiz Dergisi)
Video assistant referee system is the name of a system which the referee is warned in doubtful situations by other referees who watch the game from various technological cameras during a football game. In this system video assistant referees warn the referee with headphone after analysing the position in detail with high-tech cameras and the referee analyses the position (if he wants) by watching on a monitor on the touchline and decides. Jean Baudrillard, one of the most significant thinkers of the twentieth century, thinks that the system produces various technologies on behalf of goodness with integral reality discourse which has a theoretical qualification and these technologies are seemingly useful for the people however in reality the system patronizes everything, and humanitarian qualifications are destroyed. This study aims to contribute to a better understanding of integral reality which contains abstract discourses with video assistant referee system which contains concrete perspectives. Within this scope, football competitions in which Metropolitan Municipality Erzurumspor one of the Sportoto Super League teams played in 2018-2019 season, in Turkey has been examined.